2014
DOI: 10.1186/1744-9081-10-26
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in genes implicated in dopamine, serotonin and noradrenalin metabolism suggest association with cerebrospinal fluid monoamine metabolite concentrations in psychosis

Abstract: BackgroundHomovanillic acid (HVA), 5-hydroxyindoleacetic acid (5-HIAA) and 3-methoxy-4-hydroxyphenylglycol (MHPG) are the major monoamine metabolites in the central nervous system (CNS). Their cerebrospinal fluid (CSF) concentrations, reflecting the monoamine turnover rates in CNS, are partially under genetic influence and have been associated with schizophrenia. We have hypothesized that CSF monoamine metabolite concentrations represent intermediate steps between single nucleotide polymorphisms (SNPs) in gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…However, we failed to identify significant changes in metabolites of this pathway in blood, and the majority of these metabolites were not detectable in human CSF (5-hydroxytryptophan, kynurenine and tryptophan being the exceptions). Previous studies have shown that single nucleotide polymorphisms in tryptophan 5-monooxygenase could be linked to neuropsychiatric disorders [56]. A substantial increase in 5-hydroxytryptophan is seen in aromatic L-amino acid decarboxylase deficiency, where patients are rendered in a vegetative state [57] and treatments with 5-hydroxytryptophan have been used to treat depression caused by serotonin deficiencies [58].…”
Section: Discussionmentioning
confidence: 99%
“…However, we failed to identify significant changes in metabolites of this pathway in blood, and the majority of these metabolites were not detectable in human CSF (5-hydroxytryptophan, kynurenine and tryptophan being the exceptions). Previous studies have shown that single nucleotide polymorphisms in tryptophan 5-monooxygenase could be linked to neuropsychiatric disorders [56]. A substantial increase in 5-hydroxytryptophan is seen in aromatic L-amino acid decarboxylase deficiency, where patients are rendered in a vegetative state [57] and treatments with 5-hydroxytryptophan have been used to treat depression caused by serotonin deficiencies [58].…”
Section: Discussionmentioning
confidence: 99%
“…Enzymes involved in 5‐HT metabolism are less well‐studied than 5‐HT transporters and HTRs. However, they can importantly affect the concentration of 5‐HT breakdown products (Andreou et al, ). Some enzymes involved in 5‐HT metabolism also play a role in other neurotransmitter pathways, such as MAOA which breaks down dopamine as well as 5‐HT (Qiu et al, ).…”
Section: Serotonin Pathway Genes Associated With Szmentioning
confidence: 99%
“…Other studies have examined the changes in metabolites associated with polymorphisms confirming that higher activity alleles show more metabolism of dopamine, noradrenaline and serotonin (Aklillu et al, 2009, Andreou et al, 2014. Elevated MAO activity had already been observed in AD-type dementia in 1980 (Adolfsson et al, 1980).…”
Section: Mao Influences the Monoamine Levels In Brainmentioning
confidence: 99%